Combined real‐time PCR and galactomannan surveillance improves diagnosis of invasive aspergillosis in high risk patients with haematological malignancies. (11th March 2013) - Rogers, Thomas R.; Morton, Charles Oliver; Springer, Jan; Conneally, Eibhlin; Heinz, Werner; Kenny, Claire; Frost, Susanna; Einsele, Hermann; Loeffler, Juergen
Summary Invasive aspergillosis (IA) is a leading complication of intensive treatment for haematological malignancies. Earlier diagnosis should facilitate effective antifungal therapy and prevent progression to invasive disease, which is often lethal. Polymerase chain reaction (PCR) assays, targeting the 28S and ITS ribosomal gene regions respectively, were evaluated for early detection of Aspergillus DNA and for diagnostic utility in patients receiving treatment in two busy haematopoietic stem cell transplant centres. Patients undergoing intensive chemotherapy, autologous or allogeneic transplant were eligible for inclusion in the study. EDTA blood and serum samples for circulating Aspergillus biomarkers, including galactomannan (GM), were collected twice‐weekly on a prospective basis from all study patients who were categorized according to international consensus criteria for defining invasive fungal disease (IFD). Of 278 patients recruited there were 44 probable IA cases and only one proven case. Moderate sensitivity and specificity, poor positive predictive value (50–80%), but good negative predictive value (>80–90%) were common to both PCR assays. Overall biomarker performance could be improved by combining positive results of either PCR assay with GM taken within a 12‐d period. The addition of PCR to GM monitoring in high‐risk patients with haematological malignancies provides greater diagnostic accuracy in invasive aspergillosis.